2009
DOI: 10.1136/vetrec.165.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial carriage of computer keyboards in veterinary practices in Scotland

Abstract: STUDIES in human hospitals have shown that objects such as door handles and computer keyboards can act as sources of contamination with bacteria such as meticillin-resistant Staphylococcus aureus (MRSA) and Campylobacter (Bures and others 2000, Kassem and others 2007). The aim of this study was to investigate whether bacteria were present on keyboards used in consulting rooms in veterinary practices in the UK, and to identify whether these keyboards could be a source of pathogenic bacteria that could affect an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 7 publications
3
16
0
Order By: Relevance
“…The high level of microbial load seen in this study which includes: Staphylococcus aureus, E. coli, Bacillus subtilis, Pseudomonas sp., Rhizopus sp.and Aspergillus niger is in line with the study of Fraser and Girling (2007), who reported that keyboards of ATM harbored more bacteria than computer keyboards and this may be due to the fact that they are exposed to many users, environmental factors such as rain and climatic factors such as wind. This study is also in conformity with Anastasiades et al, (2009) Mbajiuka (2015).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The high level of microbial load seen in this study which includes: Staphylococcus aureus, E. coli, Bacillus subtilis, Pseudomonas sp., Rhizopus sp.and Aspergillus niger is in line with the study of Fraser and Girling (2007), who reported that keyboards of ATM harbored more bacteria than computer keyboards and this may be due to the fact that they are exposed to many users, environmental factors such as rain and climatic factors such as wind. This study is also in conformity with Anastasiades et al, (2009) Mbajiuka (2015).…”
Section: Discussionsupporting
confidence: 87%
“…The number of microorganisms present on a surface is amongst the microbe-associated factors that determine whether an infection will occur or not. Apart from the number of microorganisms, the type and quality of microorganisms present on a surface is also an important factor to know if an infectious outbreak will occur or not (Fraser and Girling, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Other bacteria like Enterobacter spp and Pseudomonas aeruginosa, were the least frequent bacterial contaminants, their presence on environmental surfaces like ATMs is a cause for some alarm, because they have been shown to possess the potential to cause infection, especially in a hospital settings [8]. In different studies, each of these organisms has been implicated either as a major contaminant or as the most prevalent pathogenic bacteria recovered [11,29,25].…”
Section: Discussionmentioning
confidence: 99%
“…Colonization of objects by pathogenic organisms has been reported as a potential vehicle for their transmission (Neely and Maley, 2000;Gerba, 2005;Famurewa and David, 2009;Ulger et al, 2009;Fraser and Girling, 2009;Gholamreza et al, 2009). Furthermore, microorganisms found to contaminate fomites have also been shown to persist on environmental surfaces for varying periods of time ranging from hours to months (French et al, 2004).…”
Section: Ajidmentioning
confidence: 99%